2017
DOI: 10.3389/fpsyg.2017.00963
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Micro-relations Underpinning Familiarity Detection in Dynamic Displays Containing Multiple Objects

Abstract: We identified the important micro-relations that are perceived when attempting to recognize patterns in stimuli consisting of multiple dynamic objects. Skilled and less-skilled participants were presented with point light display sequences representing dynamic patterns in an invasion sport and were subsequently required to make familiarity based recognition judgments in three different conditions, each of which contained only a select number of features that were present at initial viewing. No differences in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 37 publications
5
13
1
Order By: Relevance
“…Surprisingly and in contrast to the majority of previous laboratory-based research (Gorman et al, 2012(Gorman et al, , 2015Magnaguagno & Hossner, 2020;North et al, 2009North et al, , 2011North et al, , 2017Sherwood et al, 2019;Williams et al, 2006), the findings of Ex-periment1 showed thatplayers ofa higher expertise level were not explicitly more aware of the pattern compared to their counterparts (. Fig.…”
Section: Overall Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Surprisingly and in contrast to the majority of previous laboratory-based research (Gorman et al, 2012(Gorman et al, , 2015Magnaguagno & Hossner, 2020;North et al, 2009North et al, , 2011North et al, , 2017Sherwood et al, 2019;Williams et al, 2006), the findings of Ex-periment1 showed thatplayers ofa higher expertise level were not explicitly more aware of the pattern compared to their counterparts (. Fig.…”
Section: Overall Discussioncontrasting
confidence: 85%
“…However, the development of such skills is considerably underresearched (Williams, Fawver, Broadbent, Murphy, & Ward, 2019). So far, investigations have focused on superior performance of skilled players compared to less-skilled counterparts for situational probabilities (Abernethy, Gill, Parks, & Packer, 2001;Farrow & Reid, 2012;Helm, Cañal-Bruland, Mann, Troje, & Munzert, 2020;Magnaguagno, Zahno, Kredel, & Hossner, 2022) and pattern identification-more precisely, pattern detection (Magnaguagno & Hossner, 2020), pattern recognition (North, Williams, Hodges, Ward, & Ericsson, 2009;North, Ward, Ericsson, & Williams, 2011;Roca, Ford, McRobert, & Williams, 2013;Vater, Luginbühl, & Magnaguagno, 2019;Williams, Hodges, North, & Barton, 2006), as well as pattern recall (Gorman, Abernethy, & Farrow, 2012North, Hope, & Williams, 2017;Raab & Farrow, 2015;Sherwood, Smith, & Masters, 2019;Smeeton, Ward, & Williams, 2004;van Maarseveen, Oudejans, & Savelsbergh, 2015). In contrast, the relevance of the intertwining between different perceptual-cognitive skills has received far less attention; even though it has been claimed that it is the interaction of these skills that facilitates decision making (Roca & Williams, 2016;Williams et al, 2017).…”
Section: Data Availabilitymentioning
confidence: 99%
“…The vast majority of existing papers have focused exclusively on the training of cue usage, with hardly any research focusing on the trainability of other perceptual-cognitive skills such as pattern recognition (for an exception, see North, Hope, & Williams, 2017) and the use of contextual information(for an exception, see Williams, Herron, Ward, & Smeeton, 2008). Williams, Hodges, & Ward, 2005).…”
Section: How Scientists Have Attempted To Develop Training Programs Tmentioning
confidence: 99%
“…In sporting contexts, identification ability is imperative, as it allows teammates to recognize each other and misidentification or a delay in recognition may result in lost scoring or passing opportunities. Passing affordances, for example, stem from classifying players as teammates or opponents ( North et al, 2017 ), and identifying the potential recipient to determine if they are the best tactical option to receive a pass. This is done by differentiating between relevant and irrelevant cues that can be extracted from form, uniform, and biological motion (e.g., players, spectators, and match officials).…”
Section: Introductionmentioning
confidence: 99%